O031/#777 Lymphadenectomy in endometrioid ovarian carcinoma patients with early stage disease: results from the leopard trial. (4th December 2022) - Grube, Marcel; Neilson, Andrea; Plante, Marie; Brummel, Koen; Kroon, Cornelis De; Schochter, Fabienne; Sideris, Michail; Heitz, Florian; Bartl, Thomas; Heublein, Sabine; Vanderhyden, Barbara; Wimberger, Pauline; et al.
Abstract : Objectives: The benefit of lymph node surgery (LNS) in early-stage endometrioid ovarian carcinoma (ENOC) is unknown. Only vague data on impact of endometrioid histotype is available. Prior studies examining the benefit of LNS in ENOC have been hampered by small numbers, and large-scale studies that consider modern classification are needed. Methods: After launching a transatlantic initiative, a cohort of 785 ENOC was assembled from 22 centers across Canada and Europe. Histotype was confirmed by central expert pathology review and immunohistochemistry, followed by extensive chart review. Complete lymphadenectomy was defined as such when at least 10 pelvic and 10 paraaortic LN were removed. Results: Chart review and histopathologic data was available from 596 patients of which in 509(85.4%) cases tumor spread was confined to the pelvis (pT1a-pT2b, M0). Grade distribution included 221/509(43.4%) G1, 212/509(41.7%) G2 and 74/509(14.5%) G3 tumors. While LNS has been omitted in 239/509(47.0%) cases, complete pelvic and paraaortic LNS was performed in 77/509(15.1%) patients. LNS was restricted to pelvic nodes in 88/509(17.3%), to paraaortic nodes in 16/509(3.1%) and to sampling procedures in 77/509(15.1%) cases. Positive nodes were found in 6/509(1.2%) patients with early-stage ENOC, all low-grade tumors were found to be node negative. Conclusions: LEOPARD results indicate that lymph node involvement is rare in early-stage ENOC, even in high grade tumors. However, the variation in lymph node surgical practice was profound. Our team initiative stands to provide a powerful statement on the value of LNS, possibly improving precision care for ENOC patients.